2020
DOI: 10.1021/acs.jpcc.0c02630
|View full text |Cite
|
Sign up to set email alerts
|

Silver–Gold Bimetallic Alloy versus Core–Shell Nanoparticles: Implications for Plasmonic Enhancement and Photothermal Applications

Abstract: Bimetallic plasmonic nanoparticles enable tuning of the optical response and chemical stability by variation of the composition. The present numerical simulation study compares Ag-Au alloy, Ag@Au core-shell, and Au@Ag core-shell bimetallic plasmonic nanoparticles of both spherical and anisotropic (nanotriangle and nanorods) shapes. By studying both spherical and anisotropic (with LSPR in the near-infrared region) shapes, cases with and without interband transitions of Au can be decoupled. Explicit comparisons … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 62 publications
2
65
0
Order By: Relevance
“…Blommaerts et al (2019) showed that these AuxAg1 − x NPs consist of a gold-enriched core and a silver-enriched shell, due to the formation mechanism of the modified Turkevich synthesis based on gold nucleus seeds [33]. Borah et al ( 2020) recently revealed a similar progressive decrease in λmax at lower Au contents for 60 nm Au@Ag core-shell NPs using numerical simulations [34]. The linear combination of all NPs provides a valuable strategy to achieve a strong optic response and a broad absorption band as shown in the inset of Figure 1a.…”
Section: Pristine Plasmonic 'Rainbow' Photocatalystsmentioning
confidence: 96%
“…Blommaerts et al (2019) showed that these AuxAg1 − x NPs consist of a gold-enriched core and a silver-enriched shell, due to the formation mechanism of the modified Turkevich synthesis based on gold nucleus seeds [33]. Borah et al ( 2020) recently revealed a similar progressive decrease in λmax at lower Au contents for 60 nm Au@Ag core-shell NPs using numerical simulations [34]. The linear combination of all NPs provides a valuable strategy to achieve a strong optic response and a broad absorption band as shown in the inset of Figure 1a.…”
Section: Pristine Plasmonic 'Rainbow' Photocatalystsmentioning
confidence: 96%
“…From an atomistic perspective we therefore also see that the classical way of treating an alloy without any resolution at the atomic level does not introduce any significant error for the SPR of larger systems calculated using classical methods. 44,48,53 Furthermore we see that with good size correction the classical methods for alloys can safely be extended to small systems down to 4-5 nm. For alloys where on of the constituents is very dominating, above 90 percent, even smaller systems can be safely simulated.…”
Section: Statistical Analysis Of Modelmentioning
confidence: 79%
“…where P is any property. 41 We are here particularly interested in examining if Vegard's law also holds true for the progression of the position of the SPR with mixing of the constituents as indicated in other studies 35,[42][43][44][45][46][47][48][48][49][50][51] for alloys and to some extent core shells or if this is geometry dependent as experiments on nano discs predict. 52 Since the polarizability or extinction cross section differs for Au and Ag it would also be of interest to see if the strength of the response to an external field also follow Vegard's law since the strength of the response determines strength of the local electric field from the SPR.…”
Section: Include All Properties Of Alloysmentioning
confidence: 94%
“…For photothermal applications, nanoparticles should possess narrow LSPR with high absorption within the biological window. Since gold has a smaller real part and greater imaginary part of the dielectric function, less polarized charges and more plasmonic damping are produced by Au NPs compared to Ag NPs 59 , 60 . In other words, the Au-LSPR always occurs at a higher wavelength as compared with the ones calculated for the Ag NP.…”
Section: Resultsmentioning
confidence: 99%